2021
DOI: 10.1097/nmd.0000000000001434
|View full text |Cite
|
Sign up to set email alerts
|

Is Ignorance Bliss? Examining the Effect of News Media Exposure on Anxiety and Depression During the COVID-19 Pandemic

Abstract: There has been a widespread increase in affective disorders after the emergence of the COVID-19 pandemic. In the current study, we investigated the effects of exposure to and perceived accuracy of news media and demographic characteristics on anxiety and depressive symptoms. We conducted an online survey of US adults (N = 480) using hierarchical linear regression models to understand the predictive roles of duration and frequency of news media exposure, as well as the perceived accuracy of COVID-19 portrayal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Despite this, contrary to our assumptions, psychological disorder did not moderate the relationship between concern for war and mental health. Similarly, and in line with the hypothesis of Hoyt et al (2022), the results of this study showed a significant and negative effect of the frequency with which people inform themselves about the war on stress and anxiety/depression levels. But despite this, the frequency of following war news did not moderate the relationship between the concern for war and stress and anxiety/depression levels.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Despite this, contrary to our assumptions, psychological disorder did not moderate the relationship between concern for war and mental health. Similarly, and in line with the hypothesis of Hoyt et al (2022), the results of this study showed a significant and negative effect of the frequency with which people inform themselves about the war on stress and anxiety/depression levels. But despite this, the frequency of following war news did not moderate the relationship between the concern for war and stress and anxiety/depression levels.…”
Section: Discussionsupporting
confidence: 89%
“…The negative psychological effects of continued exposure to information about war have contributed to an overall increase in psychopathology, mental health problems, psychosocial dysfunction, self-destruction, and other mental disorders that pose a disease burden for the entire society (Rozanov et al, 2019). Recently, Hoyt et al (2022) revealed that frequency of exposure to news of traumatic events, such as the COVID-19 pandemic, was a predictor for greater anxiety and depression among United States adults.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it also aligns with the most recent studies conducted on university students involved in war contexts [22] and, in particular, also with those carried out in places that are not directly involved in an armed conflict [48,49]. Considering the studies that reveal the link between media hyperexposure to distressing information/images and mental suffering [18,31] and, in particular, those specifically referring to images of war [27,29], the relationship between Fear of War and Psychological Distress-revealed in this study-could also be associated to the compulsive search for war-related information in young Italian adults [28], probably sustained by the high levels of uncertainty that the war is fueling. Although media hyperexposure was not investigated in the present study, it is a crucial aspect to be integrated into further research.…”
Section: Discussionsupporting
confidence: 81%
“…In the Italian context, young people are particularly hyperexposed to this phenomenon, as they are very active on social networks and use them to seek information on this conflict [28]. The literature also reports that daily exposure to images and information that are too distressing can fuel states of uncertainty and fear [27,29], as well as depressive, anxious, and post-traumatic symptoms even in subjects who are not directly involved [18,26,30], as already highlighted with reference to other potentially traumatic collective phenomena, including the recent pandemic [31,32]. Thus, in a historical moment in which youth distress has been reported to be growing for some time [33,34] and has been particularly increased by the pandemic trauma-so much so that, in Italy, there is talk of a youth emergency in terms of mental health [2][3][4]35]-war risks becoming a further potentially traumatic element that adds to specific contemporary sources of unease [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Among Israeli adults, the frequency of news consumption increased significantly during the 2014 Gaza war compared with the pre-war period, and it was associated with anxiety, hyperarousal, and sleeping disorders [ 42 ]. Recently, Danielle et al, 2022, revealed that frequency of exposure to COVID-19 pandemic-related news was a predictor for greater anxiety and depression among US adults during the first wave in 2020 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%